COMPLICATED JEJUNAL DIVERTICULA AS SURGICAL EMERGENCY: EXPERIENCE AT A TERTIARY CARE HOSPITAL IN PESHAWAR, PAKISTAN - Ahmed, Ijaz; Naeem, Mohammad; Samad, Ambreen; Nasir, Amir; Aman, Zahid; Ahmed, Siddique; Manan, Fazal (Journal of Ayub Medical College Abbottabad, 2010)
Background: Diverticula of small intestine are rare. Jejunal diverticula can be single or multiple. Diverticula in the jejunum tend to be large and multiple. Clinically they may be asymptomatic or may give rise to symptoms like pain, flatulence and borborygmi, may produce malabsorption syndrome or may present in emergency with different acute pathologies like perforation, haemorrhage, obstruction, enterolith formation and inflammation. The Objective was to see the pattern of complications in jejunal diverticula presenting as a surgical emergency. Methods: This descriptive study was conducted at Surgical Units of the 3 tertiary care Hospitals of Peshawar, for 7 years from January 1, 2002 to December 31, 2008. Study included all patients presenting to and admitted in Surgical Unit, Hayatabad Medical Complex, Peshawar with complicated jejunal diverticula during the above mentioned period. Name, age, sex, other relevant data, history and examination findings and results of investigation were recorded. Uncomplicated jejuna diverticula were excluded from study. The operative findings and the type of complication were recorded. Results: Ten patients were admitted during 7 years of study. Out of all patients 9 were male and 1 was female. Eight out of 10 patients presented with perforation of diverticula while 1 patient had severe inflammation of diverticulum causing pain, ileus and acute abdomen. One patient had acute pain due to adhesion formation. Conclusion: It is seen that complicated jejunal diverticulae are quite rare and the most common complication is perforation. Inflammation and adhesion are other complications with which jejunal diverticula presented during this study. Keywords: jejunal diverticula, perforation, diverticulitis, complication